Relationship of Cellular Oxidant and Antioxidant Status with Disease Activity in Patients with Rheumatoid Arthritis - Hilal Kocabaş; Volkan Kocabaş; Sadık Büyükbaş; Ali Sallı; Hatice Uğurlu (Archives of Rheumatology, 2010)
Objective: In recent years, increasing attention has been given to the role of reactive oxygen metabolites in the pathogenesis of inflammatory diseases such as rheumatoid arthritis (RA). The aim of this study was to elucidate plasma and especially erythrocyte oxidant and antioxidant status in RA patients and to assess the relationship between disease activity scores (evaluated by Disease Activity Score (DAS) 28 as mild, moderate and severe) and antioxidant status. Materials and Methods: Fasting blood samples were obtained from 50 RA patients and 26 control subjects. DAS28 was used to evaluate the activity. Plasma and erythrocyte levels of malondialdehyde (MDA), xanthine oxidase (XO) and superoxide dismutase (SOD) were investigated in both groups. Results: The plasma levels of MDA and XO and erythrocyte levels of MDA and SOD were significantly higher in RA patients than in control subjects. Although increases in plasma MDA levels in mild and moderate and erythrocyte MDA levels in mild activity groups of RA were not significant (p>0.05), plasma MDA levels in severe (p=0.001) and erythrocyte MDA levels in moderate and severe activity groups of RA were significantly higher (p<0.001). Whereas plasma SOD levels showed no significant change (p=0.241), erythrocyte SOD levels were significantly increased in RA patients (p<0.001). Although increase in erythrocyte SOD activity in mild RA was not significant, it was significant in moderate and severe RA (p=0.002 and p<0.001, respectively). Conclusion: These results suggest that increased plasma and erythrocyte MDA levels in RA patients, especially in those with severe activity, indicate an increased oxidative stress due to inflammation. Nonetheless, an increase particularly in erythrocyte SOD activity in moderate and severe RA patients suggests that the cellular antioxidant system might counterbalance the oxidant status in RA patients. (Turk J Rheumatol 2010; 25: 141-6)